Political Polarization Affects Households' Financial Decisions: Evidence from Home Sales - MCCARTNEY, W. BEN; ORELLANA‐LI, JOHN; ZHANG, CALVIN (Journal of Finance, 2024)
ABSTRACT Political identity and partisanship are salient features of today's society. Using deeds records and voter rolls, we show that current residents are more likely to sell their homes when opposite‐party neighbors move in nearby than when unaffiliated or same‐party neighbors do. This is especially true when the new neighbors are politically active, consistent with an animosity between parties mechanism. We conclude that affective polarization is not limited to purely political settings and affects one of the household's most important financial decisions, their home transactions.